PSUP: A Planetary SUrface Portal. (January 2018) - Poulet, F.; Quantin-Nataf, C.; Ballans, H.; Dassas, K.; Audouard, J.; Carter, J.; Gondet, B.; Lozac'h, L.; Malapert, J.-C.; Marmo, C.; Riu, L.; Séjourné, A.
Abstract: The large size and complexity of planetary data acquired by spacecraft during the last two decades create a demand within the planetary community for access to the archives of raw and high level data and for the tools necessary to analyze these data. Among the different targets of the Solar System, Mars is unique as the combined datasets from the Viking, Mars Global Surveyor, Mars Odyssey, Mars Express and Mars Reconnaissance Orbiter missions provide a tremendous wealth of information that can be used to study the surface of Mars. The number and the size of the datasets require an information system to process, manage and distribute data. The Observatories of Paris Sud (OSUPS) and Lyon (OSUL) have developed a portal, called PSUP (Planetary SUrface Portal), for providing users with efficient and easy access to data products dedicated to the Martian surface. The objectives of the portal are: 1) to allow processing and downloading of data via a specific application called MarsSI (Martian surface data processing Information System); 2) to provide the visualization and merging of high level (image, spectral, and topographic) products and catalogs via a web-based user interface ( MarsVisu ), and 3) to distribute some of these specific high level data with an emphasis on products issued by the science teams of OSUPS and OSUL. As the MarsSI service is extensively described in a companion paper (Quantin-Nataf et al., companion paper, submitted to this special issue), the present paper focus on the general architecture and the functionalities of the web-based user interface MarsVisu. This service provides access to many data products for Mars: albedo, mineral and thermal inertia global maps from spectrometers; mosaics from imagers; image footprints and rasters from the MarsSI tool; high level specific products (defined as catalogs or vectors). MarsVisu can be used to quickly assess the visualized processed data and maps as well as identify areas that have not been mapped yet. It also allows overlapping of these data products on a virtual Martian globe, which can be difficult to use collectively. The architecture of PSUP data management layer and visualization is based on SITools2 (Malapert and Marseille, 2012 ) and MIZAR (Module for Interactive visualiZation from Astronomical Repositories) respectively, two CNES generic tools developed by a joint effort between the French space agency (CNES) and French scientific laboratories. Future developments include the addition of high level products of Mars (regional geological maps, new global compositional maps…) and tools (spectra extraction from hyperspectral cubes). Ultimately, PSUP will be adapted to other planetary surfaces and space missions in which the French research institutes are involved. Highlights: A web portal, called PSUP (Planetary SUrface Portal) is presented. It allows processing and downloading of data via a specific application called MarsSI . It allows the visualization and merging of high level products and catalogs via a web-based user interface MarsVisu . It allows the distribution of some of these specific high level data.